2017
DOI: 10.1021/acs.cgd.6b01701
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Structural Design of Crystalline Drug-Excipient Composite Microparticles via Microfluidic Droplet-based Processing

Abstract: We present a simple, bottom up method for the structural design of solid microparticles containing crystalline drug and excipient using microfluidic droplet-based processing. In a model system comprising 5-methyl-2-[(2-nitrophenyl)­amino]-3-thiophenecarbonitrile (ROY) as the drug and ethyl cellulose (EC) as the excipient, we demonstrate a diversity of particle structures, with exquisite control over the structural outcome at the single-particle level. Within microfluidic droplets containing drug and excipient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The drug-release profiles obtained with neat naproxen and naproxen–ethyl cellulose microparticles of drug–polymer ratios 2.5, 1.25, 0.75, and 0.625 are provided in Figure . The wide range and variety of dissolution profiles obtained crucially highlights the applicability of the method to formulate functional drug-containing microparticles by tuning particle composition; we note that similar drug-release trends have been seen from in vitro release studies of MK-8591 and carbamazepine drug release from nonerodible poly­(ethylene vinyl acetate) matrix implants and ethyl cellulose microparticles at varying drug–polymer loads, respectively. These studies have demonstrated that drug release from insoluble matrices is diffusion-controlled.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The drug-release profiles obtained with neat naproxen and naproxen–ethyl cellulose microparticles of drug–polymer ratios 2.5, 1.25, 0.75, and 0.625 are provided in Figure . The wide range and variety of dissolution profiles obtained crucially highlights the applicability of the method to formulate functional drug-containing microparticles by tuning particle composition; we note that similar drug-release trends have been seen from in vitro release studies of MK-8591 and carbamazepine drug release from nonerodible poly­(ethylene vinyl acetate) matrix implants and ethyl cellulose microparticles at varying drug–polymer loads, respectively. These studies have demonstrated that drug release from insoluble matrices is diffusion-controlled.…”
Section: Resultssupporting
confidence: 53%
“…Kawashima et al introduced the concept of spherical crystallization nearly three decades ago; this is a particularly facile process of granulation, in which spherical crystal agglomerates are directly formed during crystallization via the introduction of a bridging liquid or by conducting antisolvent crystallization within transient droplets (quasi emulsions) formed from miscible solvent pairs using high shear and agitation. , The main challenge of the aforementioned methods when conducted in agitated vessels is the coarse control over particle sizes, as the operation is sensitive to multiple scale-up factors such as mixing efficiency, impeller and vessel geometry, and inlet configuration. Some recent studies that have addressed this challenge couple microfluidics with drug crystallization, allowing for facile production of neat drug and also drug-excipient microparticles with tunable sizes and structures using microfluidic evaporative crystallization. In these demonstrations, monodisperse drug or drug-excipient mixture loaded droplets are generated in immiscible continuous fluids and subjected to solvent removal via evaporation to induce drug supersaturation for direct particle formation. Besides evaporative crystallization, recent demonstrations by Watanabe et al .…”
Section: Introductionmentioning
confidence: 99%
“…The production of sphere-shaped cellulose-based microparticles can be performed by emulsification processes [ 93 , 112 , 113 , 114 , 115 ], and microfluidics technology [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ], as well as other less common techniques, namely spray-assisted techniques [ 126 , 127 , 128 , 129 , 130 ], and the LbL assembly [ 131 , 132 ]. Concerning the cellulosic substrate, the majority of the studies reported the utilization of cellulose derivatives, such as CMC [ 120 , 131 ], CA [ 114 , 119 ] and EC [ 123 , 124 , 133 , 134 ], but also pristine vegetable cellulose [ 112 , 135 , 136 , 137 ], bacterial nanocellulose [ 116 , 117 , 118 ] and microcrystalline cellulose (MCC) [ 93 , 115 , 138 , 139 ]. The preference for cellulose derivatives to generate microparticles was anticipated given their solubility in water or in most common organic solvents, which translates into simpler processability.…”
Section: Production Of Spherical Cellulose-based Microparticlesmentioning
confidence: 99%
“…The microfluidic technology is another methodology that is being used to fabricate sphere-shaped cellulose-based microparticles. Table 2 summarizes some of the most recent examples of micro-sized particles based on pure cellulose [ 116 , 117 , 118 , 125 ], and cellulose derivatives, such as CA [ 119 ], CMC [ 120 ], EC [ 123 , 124 ] and TEMPO-oxidized CNFs [ 155 ], produced by microfluidics.…”
Section: Production Of Spherical Cellulose-based Microparticlesmentioning
confidence: 99%
“…In all these applications, cellulose as a solid phase provides a large surface area that may separate chemicals from flowing liquids due to cellulose active functional groups. In chromatography [14], protein purification [15], and drug delivery [16][17][18][19], cellulose beads can be utilized as the stationary phase. Papermaking and the synthesis of micro fibrillated cellulose have both employed partially or considerably fibrillated cellulose.…”
Section: Introductionmentioning
confidence: 99%